An Overview of Recent Achievements in the Fabrication and Modification of Microfiltration Antifouling Membranes for Water Treatment - Shokufeh Pira; Safura Nazari; Azar Asadi (آب و فاضلاب, 2022)
One of the most pressing challenges confronting modern civilization is the lack of enough clean water supplies. Membrane technology has emerged as a key technology for water treatment, including fresh water, salt water, and municipal or industrial wastewater treatment, owing to its energy savings, high performance efficiency, and cost-effectiveness. However, membrane fouling, resulting from a non-specific interaction between the membrane surface and fouling agents, significantly hinders the efficient utilization of membrane technology. The fabrication of antifouling membranes is a fundamental approach to dealing with fouling issues caused by various types of fouling agents. Significant progress has been made in membrane preparation techniques and modification strategies, notably in microfiltration membranes, in recent years. While outlining the key strategies for modifying antifouling microfiltration membranes, the present review highlights recent achievements in the mentioned field, which provides more details related to the fabrication and preparation techniques and enhances performance parameters of these membranes. Microfiltration nanocomposite membranes modified by blending method can be considered an emerging technology capable of converting laboratory/pilot scale to a reliable commercial technology due to their high performance efficiency and good antifouling properties among all modification methods covered in this study. While using modification techniques (blending, surface modification, interfacial polymerization, sol-gel, and electrospinning) to better manage fouling in microfiltration membranes has certain benefits in terms of boosting performance, it also has drawbacks. Therefore, further optimization of modifying methods with the aim of commercializing modified microfiltration membranes is essential.